Phase Calibration of On-Chip Optical Phased Arrays via Interference Technique - Haiyang Zhang; Zixuan Zhang; Chao Peng; Weiwei Hu (IEEE Photonics Journal)
Optical phased arrays (OPAs) are promising in various applications owing to their excellent beam steering performance but suffer from the random initial phases ruining the beam patterns. In this work, an interference-based calibration method to align the random phases for OPA operations is proposed. Briefly, the phase differences are directly extracted from the interference fringes and used to build up the phase map. The feasibility and effectiveness of the proposed method were verified from an 8 × 8 OPA chip, in which the side-lobe suppression ratio of 10.1 dB was achieved. The proposed method can be utilized as a supplement of conventional calibration algorithms to reduce requirements for the sensitivity of the feedback system and avoid local optima, thus providing practical assistance for many OPA applications.